Eco-Friendly Digital Educational Practices That Promote Sustainability - Lenkauskaite , Edita; Souza, Caio Cesar (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The European Union initiated the creation of European Universities Alliances (EUA), which should tackle today’s world challenges by joining together the resources of Higher Education Institutions (HEI) all over Europe. These Alliances are not only solving the world’s environmental challenges, but also should face their own sustainability question, because of their project-based nature. If the European Commission hopes for at least 50 per cent mobility within the EUA, but the financial resources they generate don’t allow for the physical implementation of this, the only other option is eco-friendly digital mobility. Digital mobility is environmentally sustainable because it has an almost zero carbon footprint. Moreover, it also helps EUA to be adaptable and persistent, which are the key components of EUA sustainability.